Risk factors and outcome of Shigella encephalopathy in Bangladeshi children. - Farzana Afroze; Tahmeed Ahmed; Monira Sarmin; Abu Smsb Shahid; K M Shahunja; Lubaba Shahrin; Mohammod Jobayer Chisti (Public Library of Science (PLoS), 2017)
BACKGROUND:Although, Shigella encephalopathy, a serious extra-intestinal complication of shigellosis, significantly increases the risks of death, data are very limited on predicting factors particularly related to electrolyte profiles in children below five years of age with Shigella encephalopathy. Our objective was to determine the clinical as well as laboratory predicting factors and outcome of children with Shigella encephalopathy. METHODOLOGY/PRINCIPAL FINDINGS:In this unmatched case-control design, children aged 2-59 months having a positive stool culture for Shigella and who had their serum electrolytes been done from July 2012 to June 2015 were studied. Children with Shigella encephalopathy, defined as having abnormal mentation, constituted the cases, and those without encephalopathy constituted the controls. During the study period, we identified a total of 541 children less than five years of age, who had Shigella in their stool culture. Only 139 children fulfilled the study criteria and among them 69 were cases and 70 were controls. The cases more often had fatal outcome compared to the controls (7% vs. 0%, P = 0.02). In logistic regression analysis, the cases were independently associated with shorter duration (1.2 ± 0.4 days) of diarrhea prior to admission, dehydrating diarrhea, sepsis and hyponatremia (p<0.05 for all). Among 139 Shigella isolates, S. flexneri (88/139, 63%) and S. sonnei(34/139, 24%) were the dominant species. S. dysenteriae was not isolated throughout the study period. S.sonnei was more frequently isolated from the cases (24/69, 35%) than the controls (10/70, 14%), whereas the isolation of S. flexneri was comparable between the groups (40/69, 58% vs 48/70, 69%). A total of 94 (67.6%) isolates were resistant to trimethoprim-sulphamethoxazole, 84 (60.4%) to ciprofloxacin, 66/138 (48%) to ampicillin, 5 (3.5%) to ceftriaxone, 17 (12.2%) to mecillinum and 35 (25%) to azithromycin. CONCLUSIONS/SIGNIFICANCE:The case-fatality-rate was significantly higher among the children with Shigella encephalopathy compared to those without encephalopathy. Early identification and aggressive management of simple risk factors for Shigella encephalopathy may help to reduce morbidity and deaths in such children especially in resource-limited settings.